Water Brightness Profile Based on Tidal Current in Dumai River Estuary, Dumai City, Riau Province - Aristi, Fiona; Rifardi, Rifardi; Elizal, Elizal (Journal of Coastal and Ocean Sciences, 2021)
This research was conducted in August 2020 in the Dumai River Estuary, West Dumai District, Dumai City, Riau Province. The purpose of this study was to determine the brightness of the waters and its distribution in the waters of the Dumai River estuary. The research method used is a survey method with the determination of the sampling point using purposive sampling method at tide towards low tide and low tide towards the tide. The map is heavy using ArcMap 10.4 software and interpolated using IDW (Spatial Analyst) tools. The results showed the brightness at tide to low tide, which is around 23.5-129 cm with an average brightness of 84.3 cm. Brightness at at low tide to high tide is around 35-127.5 cm with an average brightness of 88.15 cm. Based on the map, the brightness of the waters of the Dumai River Estuary is low at the mouth of the estuary and high in the part that leads to the sea